Differences in anger depending on sport performance in table tennis players - González-Garcia, H.; Pelegrin, A.; Trinidad, A. (Journal of Human Sport & Exercise, 2020)
The aim of this study is to determine if there are differences in anger levels depending on sport performance in table tennis players. The sample consisted of 93 Spanish table tennis players, 20 players were professionals (21.50%) and 73 were amateur (78.49%). An ad hoc Sociodemographic Questionnaire and the Trait-State Anger Expression Inventory (STAXI 2), were used to measure the different variables. The results showed significant differences in external anger expression (p<.05), depending on league level where the players who took part in greater leagues showed lower levels of anger. Additionally, internal anger control (p<.05) and anger expression index (p<.05) reported significant differences depending on league level where the players who took part in greater leagues showed greater levels. It was concluded that there are differences in anger levels depending on division level. Therefore, it is important to coach players towards anger control in table tennis.